Comparison of state risk-appropriate neonatal care policies with the 2012 AAP policy statement. (April 2018) - Kroelinger, Charlan; Okoroh, Ekwutosi; Goodman, David; Lasswell, Sarah; Barfield, Wanda
Abstract Objective Compare state policies with standards outlined in the 2012 AAP Policy Statement on Levels of Neonatal Care. Study design Systematic, web-based review of publicly available policies on levels of care in all states in 2014. Infant risk information, equipment capabilities, and specialty staffing were abstracted from published rules, statutes, and regulations. Result Twenty-two states had a policy on regionalized perinatal care. State policies vary in consistency with the AAP Policy, with 60% of states including standards consistent with Level I criteria, 48% Level II, 14% Level III, and one state with Level IV. Ventilation capability standards are highly consistent (66–100%), followed by imaging capability standards (50–90%). Policy language on specialty staffing (44–68%), and subspecialty staffing (39–50%) are moderately consistent. Conclusion State policies vary in consistency, a potentially significant barrier to monitoring, regulation, uniform care provision and measurement, and reporting of national-level measures on risk-appropriate care.